Multifocal Insulinoma in Pancreas and Effect of Intraoperative Ultrasonography - Ersin Borazan; Alper Aytekin; Latif Yilmaz; Muhsin Elci; Mehmet Salih Karaca; Selim Kervancioglu; Ahmet Abdulhalik Balik (Case Reports in Surgery)
Insulinoma is the most frequently seen functional pancreatic neuroendocrine tumor. The incidence of multifocal insulinoma is lower than 10%. Its treatment is direct or laparoscopic excision. The present case was examined with the findings of hypoglycemia and hypercalcemia, and as there was high insulin and C-peptide levels the initial diagnosis was insulinoma. The case was investigated in terms of MEN 1. During preoperative screening for localization, there was one focus in the head of the pancreas in the abdominal tomography and two foci in endoscopic ultrasonography. No other focus was detected through intraoperative visual or manual palpation. However, five foci were detected during operation by intraoperative ultrasonography. The relation of masses with the main pancreatic canal was evaluated and they were excised by enucleation method. There was no recurrence during the postoperative 18-month follow-up of the patient. As a result, during treatment for insulinoma, it should be kept in mind that there might be multifocal foci. In all insulinomas, the whole pancreas should be evaluated with intraoperative ultrasonography because none of the current preoperative diagnostic methods are as sensitive as manual palpation of pancreas and intraoperative ultrasonography. The intraoperative detection of synchronous five foci in pancreas is quite a rare condition.